Implementation Of Physical Literacy Model In Physical Education, Sport And Health (PJOK) Learning In Elementary School - Fifukha Dwi Khory; Ali Maksum; Rini Ismalasari; Testa Adi Nugraha; Mohammad Fathur Rohman (JUARA : Jurnal Olahraga, 2023)
The specific objective to be achieved in this study is to apply the physical literacy model in learning physical education, sports, and health in elementary schools (PJOK SD). With the implementation of the physical literacy model in PJOK SD learning, it is hoped that there will be an increase in the quality of physical activity with moderate to high intensity (MVPA/Moderate to Vigorous Physical Activity) with the added value of specific goals from physical literacy. The research method to achieve the research objectives was an experimental pretest-posttest control group design. The research subjects to develop instruments for implementing the physical literacy model for SD PJOK learning were physical education experts, student development experts, sports coaching experts, and Physical Education teachers. While the research subjects to test the instrument's reliability were fifth-grade elementary school students in the Surabaya area. Research data collection used tools developed based on literature studies on physical literacy models, FGD (Focus Group Discussion), and trials. Data analysis based on the nature and descriptive statistical research design, paired sample t-test, and independent sample test t-test. The results of this study showed that there was a significant difference between the pretest and posttest results in the control group. There was a substantial difference between the pretest and posttest results in the experimental group. There was no significant difference between the pretest results of the control group and the experimental group. However, looking at the mean between the control and experimental groups, there tends to be an increase in the experimental group. These results can help parents, trainers, and educators, especially PJOK SD teachers, conduct coaching and movement education for elementary school students. In addition, it is expected to be able to develop the competence of elementary school students as a whole.